Nilai Spiritualisme dalam Pancasila - Natya Amelya Yahya; Citra Syahrani; Usiono Usiono (International Forum of Researchers and Lecturers, 2024)
Over the years, value has been an important part of philosophical discussions, both implicitly and directly. Spiritualism is a teaching that says that the soul is the absolute reality of nature in the universe, and that the soul is the basis of the universe and provides a rational explanation. The first principle of Pancasila, Belief in One God, shows the value of spiritualism in its foundation. The value of spiritualism in its general form can be seen in the articles of the 1945 Constitution, especially Article 29 of the Amended 1945 Constitution. Spirituality focuses on a way of life, rather than abstract and speculative philosophical formulations.